Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13045-021-01033-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of geptanolimab (GB226) for relapsed or refractory peripheral T cell lymphoma: an open-label phase 2 study (Gxplore-002)

Abstract: Background Peripheral T cell lymphoma (PTCL) is a rare disease and recent approved drugs for relapsed/refractory (r/r) PTCL provided limited clinical benefit. We conducted this study to evaluate the efficacy and safety of geptanolimab (GB226), an anti-PD-1 antibody, in r/r PTCL patients. Methods We did this single-arm, multicenter phase 2 study across 41 sites in China. Eligible patients with r/r PTCL received geptanolimab 3 mg/kg intravenously eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…In 2014, with promising data of a pivotal phase II study [29] , the Chinese original innovative HDACi chidamide has been approved for the treatment of r/r PTCL. Recently, the result of a phase II clinical trial showed that an innovative anti-PD-1 antibody geptanolimab (GB226) has showed potent activity in r/r PTCL, which may provide new treatment approach for r/r PTCL patients [30] . Second, newer targets have emerged in registered clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, with promising data of a pivotal phase II study [29] , the Chinese original innovative HDACi chidamide has been approved for the treatment of r/r PTCL. Recently, the result of a phase II clinical trial showed that an innovative anti-PD-1 antibody geptanolimab (GB226) has showed potent activity in r/r PTCL, which may provide new treatment approach for r/r PTCL patients [30] . Second, newer targets have emerged in registered clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR of pembrolizumab in patients with ENKTL was 78.6% (12). A recent study reported that geptanolimab showed promising efficacy and manageable toxicity in patients with relapsed/refractory peripheral T cell lymphoma (13). Interestingly, patients with PD-L1 expression > 50% obtained more benefit from geptanolimab treatment, with an ORR of 53.3% and a median progression-free survival of 6.2 months (13).…”
Section: Pd-l1mentioning
confidence: 99%
“…A recent study reported that geptanolimab showed promising efficacy and manageable toxicity in patients with relapsed/refractory peripheral T cell lymphoma (13). Interestingly, patients with PD-L1 expression > 50% obtained more benefit from geptanolimab treatment, with an ORR of 53.3% and a median progression-free survival of 6.2 months (13). The correlations between PD-L1 expression and response to anti-PD-1 antibodies should to be further investigated in future clinical trials.…”
Section: Pd-l1mentioning
confidence: 99%
“…Arthralgia and myalgia are the most frequently reported rheumatic irAEs, but arthritis, myositis and vasculitis were observed in blood cancer ICI trials as well (Bashey et al, 2009;Khodadoust et al, 2016;Zeidan et al, 2018;Armand et al, 2019;Barta et al, 2019;D'Souza et al, 2019;Davids et al, 2020;Diefenbach et al, 2020;Mei et al, 2020;Song et al, 2020;Liu et al, 2021;Shi et al, 2021). (Table 6) These adverse events are more likely to occur in ICIs acting on the PD-1 axis and may have later onset (Chhabra and Kennedy, 2021).…”
Section: Rheumatological Toxicitymentioning
confidence: 99%
“…One patient with RR mycosis fungoides/ Sézary syndrome who was receiving pembrolizumab experienced grade 3 corneal ulcer (Khodadoust et al, 2016). Incidents of autoimmune hematologic toxicity included newly diagnosed immune thrombocytopenia during ipilimumab therapy, autoimmune hemolytic anemia grade 4 during geptanolimab therapy (anti-PD-1 mAb) and one grade 3 and one lethal case of hemophagocytic lymphohistiocytosis in clinical studies investigating pembrolizumab monotherapy in T cell lymphomas and the combination of nivolumab with azacitidine for acute myeloid leukemia patients, respectively (Davids et al, 2016;Barta et al, 2019;Daver et al, 2019;Shi et al, 2021). (Table 6)…”
Section: Other Toxicitiesmentioning
confidence: 99%